Pengaruh Kemampuan Literasi Digital Peserta Didik dan Kreativitas Guru Terhadap Prestasi Belajar Matematika Peserta Didik kelas VIII - Diah Nadila; Nursalam; Andi Dian Angriani (Alauddin Journal of Mathematics Education, 2022)
This study aims to determine the influence of students' digital literacy and teacher creativity on the achievement of learning mathematics class VIII Madrasah Tsanawiyah Negeri Gowa. This research approach uses a quantitative approach with an ex-post-facto type of research. The population in this study was class VIII MTsN Gowa students which amounted to 200 students and a sample of 67 students. Based on the results of hypothesis testing with a significance level of 5% obtained results that showed that (1) The digital literacy ability of students had a positive effect on the mathematics learning achievement of class VIII MTsN Gowa students by 12.6%, (2) Teacher creativity has a positive effect on the mathematics learning achievement of class VIII MTsN Gowa students by 10.5%, (3) The digital literacy ability of students and teacher creativity have a positive effect on the achievement of learning mathematics for class VIII MTsN Gowa students by 17.7%. Thus, if the digital literacy skills of students and teacher creativity increase, then the achievement of learning mathematics for class VIII students of Madrasah Tsanawiyah Negeri Gowa will also increase.